Analysis of Media Agenda and Framing of HIV/AIDS in Leading Newspapers of Pakistan - Dr. Shahid Hussain,; Saba Javed,; Javeria Karim, (Journal of Peace, Development and Communication, 2022)
In Pakistan, there are about 200,000 cases of HIV/AIDS and the number is increasing day by day (UNAIDS, 2020). This research study depends on the fact that media is the main source of information on health issues such as HIV/AIDS. The study investigates that at what extent the newspapers of Pakistan give coverage and various frames to the news related to HIV/AIDS. The study also explored the placements, slants, and space given in shape of length of stories given to the HIV/AIDS in the sample newspapers. The four newspapers Daily Dawn, Daily News, Daily Nawa-i-Waqt, and Daily Dunya were selected and a total of 1454 editions were observed. Each page of these newspapers was analysed for one year and a total of 161 news items were found. With the help of agenda-setting and framing theory, the study concludes that the coverage of HIV/AIDS was dissatisfactory and insufficient. The coverage was only given in months when the AIDS cases arose in Sindh. The evidence from the study shows that the stories were mostly packaged as news stories rather than editorials, columns, and letters to the editors, and unofficial sources were used predominately. With the help of the Semetko Framing Model, there were more responsibility frames used as compared to the other frames.